When evaluating b^2c^-1 for b=8 and c=4, the answer is -16
E = b^2c–1
x-a = 1/xa
E = b^2c - 1
= 8^2 x (-4)-1
= 64/-4
= -16
Angle A is 2x + 3
Angle B is 4x + 2
Angle C is 2x - 1
The three angles add up to 180
So:
2x + 3 + 4x + 2 + 2x - 1 = 180
Combine terms
8x + 4 = 180
Subtract 4
8x = 176
x = 22
Now we solve for the angles:
Angle A is 2(22) + 3 = 44 + 3 = 47
Angle B is 4(22) + 2 = 88 + 2 = 90
Angle C is 2(22) - 1 = 44 - 1 = 43
Quick check: 47 + 90 + 43 = 180
For a polynomial of the form ax^2+bx+c rewrite the middle term as a sum of two terms whose product is a⋅c=5⋅4=20 and whose sum is b=12.
<u>Factor 12 out of 12x.</u>
5x^2+12(x)+4
<u>Rewrite 12 as 2 plus 10</u>
5x^2+(2+10)x+4
Apply the distributive property.
5x^2+2x+10x+4
Factor out the greatest common factor from each group.
Group the first two terms and the last two terms.
(5x^2+2x)+10x+4
Factor out the greatest common factor (GCF) from each group.
x(5x+2)+2(5x+2)
Factor the polynomial by factoring out the greatest common factor, 5x+25x+2.
(5x+2)(x+2)